(untitled) (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2023)
The development of information and communication technology has a great impact on various fields of life, one of which is in the dissemination of information that is socialization. Digital media is not spared from information technology, one of which is in the use of video is a medium for delivering information used in the process of socializing programs owned by certain institutions and organizations using video. As one of the elements of community institutions that is an extension of information media from the central and regional governments, PKK is a strategic forum because of its scope that can touch the inner layers of society. The dissemination of information and government programs in realizing public welfare becomes more easily spread evenly through the PKK. This training aims to assist PKK members in delivering information in the form of making short videos that will be disseminated through digital media. The method used is in the form of delivering theory and direct practice by applying composition techniques and taking pictures through a smartphone camera. The result of this training is the increasing ability of PKK members to produce videos using smartphone cameras, and can help PKK in improving the quality of information provided on digital media as a form of delivering information to the public.